The University Revolution Outline of a Processual Theory of Modern Higher Education - Lybeck, Eric (Classical and Contemporary Social Theory, 2021)
Few institutions in modern society are as significant as universities, yet our historical and sociological understanding of the role of higher education has not been substantially updated for decades. By revisiting the emergence and transformation of higher education since 1800 using a novel processual approach, this book recognizes these developments as having been as central to constituting the modern world as the industrial and democratic revolutions. This new interpretation of the role of universities in contemporary society promises to re-orient our understanding of the importance of higher education in the past and future development of modern societies. It will therefore appeal to scholars of social science and history with interests in social history and social change, education, the professions and inequalities.